حکمتِ عطیاتِ رسول ﷺ؛ ایک تحقیقی جائزہ: A Research Review of the Wisdom (purposes) of the Holy Prophet's Gifts - Yaseen, Sania; Hameed, Bareera (Al-Amīr Research Journal for Islamic Studies, 2020)
The religion that the Prophet ﷺ brought is a complete religion, and its teachings are for every aspect of life whether it is political life or economic life, individual life or collective life, there are rare instances of his guidance. In the Islamic system, the issue of distribution of wealth has been given great importance. On the contrary, it seems that the whole economy is based on making this sector stable and fair. So that wealth does not accumulate in one place but circulate it through donations and gifts other than Zakat. One of the purposes of the donations of the Holy Prophet was to train the Companions. With the donations of the Holy Prophet, the concentration of wealth was eliminated, the pleasure of Allah was obtained, and the state was strengthened internally and externally Muslims became economically and socially prosperous. The Muslim Ummah needs it in the present age to adopt the highest aspect of the life of the Holy Prophet and should not accumulate wealth but should spend it in various ways on God's creation without any purpose. This paper focuses on the wisdom of gifts/Attiyaat of the Prophet ﷺ. Why the Prophet ﷺfeel the need of giving other than Zakat.